2012
DOI: 10.1007/s11442-012-0926-1
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of TRMM Multisatellite Precipitation Analysis (TMPA) in drought monitoring in the Lancang River Basin

Abstract: Drought is one of the most destructive disasters in the Lancang River Basin, which is an ungauged basin with strong heterogeneity on terrain and climate. Our validation suggested the version-6 monthly TRMM multi-satellite precipitation analysis (TMPA; 3B43 V.6) product during the period 1998 to 2009 is an alternative precipitation data source with good accuracy. By using the standard precipitation index (SPI), at the grid point (0.25°×0.25°) and sub-basin spatial scales, this work assessed the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…In order to evaluate the precipitation data (3B43) with 22 meteorological stations in Singapore from 1998 to 2014 and showed that the TRMM precipitation products performed well in accuracy [21]. Several other studies suggested that it is feasible to use TRMM precipitation data to monitor drought conditions in typical areas of China and Africa [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the precipitation data (3B43) with 22 meteorological stations in Singapore from 1998 to 2014 and showed that the TRMM precipitation products performed well in accuracy [21]. Several other studies suggested that it is feasible to use TRMM precipitation data to monitor drought conditions in typical areas of China and Africa [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, satellite data become available for estimating precipitation over large areas with spatial and temporal consistency (Gao and Liu 2013). It has been demonstrated that satellite derived data have great potential in accurate mapping of precipitation pattern in the Tibetan Plateau (Anders et al 2006;Hao et al 2011;Jia et al 2011;Ji and Chen 2012;Zeng and Li 2012;Qi et al 2013). We consider that the high-resolution precipitation pattern so worked out should be well elucidated.…”
mentioning
confidence: 99%
“…Through combining multi-sensor microwave and infrared data with different algorithms, a few satellite-based global precipitation products, like TRMM Multi-satellite Precipitation Analysis (TMPA) (Huffman et al, 2007) and the latest Global Precipitation Measurement (GPM) mission (Hou et al, 2014), have been generated and investigated with great potentials for flood/drought monitoring (Hong et al, 2007;Zeng et al, 2012;Zhao et al, 2015). The satellite-based evapotranspiration (ET) can be successfully estimated in real-time as given the real-time inputs from Moderate Resolution Imaging Spectroradiometer (MODIS) and surface radiation products derived from geostationary satellites (Tang et al, 2009c).…”
Section: Hydrological Monitoring Observations and Data Assimilationmentioning
confidence: 99%